Mounier–Kuhn syndrome: a case of tracheal smooth muscle remodeling. Issue 2 (29th December 2016) - Cook, Daniel P.; Adam, Ryan J.; Abou Alaiwa, Mahmoud H.; Eberlein, Michael; Klesney‐Tait, Julia A.; Parekh, Kalpaj R.; Meyerholz, David K.; Stoltz, David A.
Key Clinical Message: Mounier–Kuhn syndrome is a rare clinical disorder characterized by tracheobronchial dilation and recurrent lower respiratory tract infections. While the etiology of the disease remains unknown, histopathological analysis of Mounier–Kuhn airways demonstrates that the disease is, in part, characterized by cellular changes in airway smooth muscle. Abstract : Mounier–Kuhn syndrome is a rare clinical disorder characterized by tracheobronchial dilation and recurrent lower respiratory tract infections. While the etiology of the disease remains unknown, histopathological analysis of Mounier–Kuhn airways demonstrates that the disease is, in part, characterized by cellular changes in airway smooth muscle.